The development & implementation of housing action trust policy - Tiesdell, Steven (1999)
This thesis examines the development and implementation of Housing Action Trust (HAT) policy, with a particular emphasis on the theme of choice. When first announced, the Secretary of State for the Environment, Nick Ridley, argued that HATs would form the ‘cutting edge’ of the Government's urban regenerationin itiatives. In practice, as only six HATs were ever established, they became something much more marginal and experimental. HAT policy therefore represents a curious episode in the development of housing policy in England. The 1980s Conservative Government's political ideology had been particularly influenced by the New Right and their critique of the welfare state, which inter alia called for the removal of the local authority monopoly in the rented housing sector through the demunicipalisation of local authority housing. The first policy instrument to demunicipalise council housing was a statutory right-to-buy (RTB) for council tenants introduced in 1980. During the late 1980s, three further exit mechanisms were introduced: Tenants' Choice, HATs and voluntary transfers. Proposals for HATs were met with fierce opposition from the Labour party, local authorities and tenants. None of the first six areas intended to be designated as HATs were implemented. In March 1991, however, the first successful HAT ballot occurred in Hull, followed by a second in the London Borough of Waltham Forest in July 1991 and a third in Liverpool in August, 1992. In total six HATs were established. Chapter Two outlines the research agenda. Chapter Three discusses the major developments in housing policy during the 1980s. Building on Chapters One and Three, Chapter Four focuses specifically on HAT policy. Chapters Five to Seven examine HAT practice, with each Chapter focusing on one of the first three HATs. Chapter Eight draws conclusions.